1994
DOI: 10.1104/pp.106.3.863
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Inflorescence Meristems Is Controlled by Developing Fruits in Arabidopsis

Abstract: ~~~The relationship between fruit development and the proliferative capacities of inflorescence meristems has been examined in Arabidopsis fhaliana. In the wild-type Landsberg erecta (Ler) line, flower production ceases coordinately on all inflorescence branches by a process we have designated global proliferative arrest (CPA). Morphological studies indicate that CPA involves a cessation of proliferative activity at the meristems, but a retention of the structural characteristics of the proliferating meristems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
150
0
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 23 publications
17
150
0
16
Order By: Relevance
“…The sequential production of flowers in Arabidopsis eventually stops once a certain number of fruits (under given growth conditions) have been produced (Hensel et al, 1994;Noodén and Penney, 2001). We found that sterile plants produced many more ovaries and axillary branches than fertile ones over their lifetimes ( Fig.…”
Section: Plant Fertility Influences Meristematic Activity and Eventuamentioning
confidence: 72%
See 3 more Smart Citations
“…The sequential production of flowers in Arabidopsis eventually stops once a certain number of fruits (under given growth conditions) have been produced (Hensel et al, 1994;Noodén and Penney, 2001). We found that sterile plants produced many more ovaries and axillary branches than fertile ones over their lifetimes ( Fig.…”
Section: Plant Fertility Influences Meristematic Activity and Eventuamentioning
confidence: 72%
“…We found that sterile plants produced many more ovaries and axillary branches than fertile ones over their lifetimes ( Fig. 1; see also Hensel et al [1994] and Noodén and Penney [2001]). Under given growth conditions, fruit production leads to a characteristic arrest of growing inflorescences visible through the production of terminal clusters of nonmaturing flower buds (Fig.…”
Section: Plant Fertility Influences Meristematic Activity and Eventuamentioning
confidence: 91%
See 2 more Smart Citations
“…This increase in final height is unexpected considering that the Arabidopsis GID1 genes act as positive regulators of stem elongation. It is conceivable that this increase in stem elongation in gid1a-1 gid1b-1 is an indirect consequence of the reduced fertility (Hensel et al, 1994) observed in this mutant (see below; Table 1). …”
Section: Vegetative Growth and Developmentmentioning
confidence: 99%